Pendampingan Pembelajaran Al-Qur’an Metode Iqro’ Di Dusun Besowo Timur Desa Besowo Kepung Kediri - Binti Munawaroh; Doni Saputra; Muhamad Wildan Fawa'id (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
Islam is a religion that uses the Qur'an and hadith as a way of life. The Qur'an commands Muslims to learn, and orders learning by reading since, the verse was first revealed to the Prophet Muhammad SAW, namely in the Qur'an surah Al-'Alaq verses 1-5. a must for every Muslim and we must be able to read it correctly and tartil. This service-based research aims to assist in learning to read the Koran so that they can read the Koran correctly and tartil, especially the residents of Sumberjo Hamlet, Besowo Village. This research uses the PAR (participatory Action Research) method in which researchers take part in every activity carried out during the research. The object of research in this research is the residents of Sumberjo Hamlet, Besowo Village. This research was conducted with the community around Sumberjo Hamlet, Besowo Village. The research begins by analyzing the needs of the residents in learning the Qur'an, then designing activities, carrying out activities and evacuating the results of the transformation of activities that have been carried out. Assistance in learning al-Qur'an using the Iqra method in order to know the correct reading and tartil as well as in mentoring is also guided by memorizing short surahs, daily prayers, pillars of ablution and ablution practices, valid requirements for prayer and prayer practices so that they can be practiced in daily life. day correctly and easily.